2000
DOI: 10.1007/s004029900132
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of blood loss using tranexamic acid in total knee and hip arthroplasties

Abstract: There have been several attempts to reduce postoperative blood loss in patients undergoing total arthroplasty. Benoni et al. reported the usefulness of tranexamic acid in total knee arthroplasty (TKA). We investigated its effect in TKA and total hip arthroplasty (THA). Blood loss was significantly reduced in patients given tranexamic acid in both the TKA and THA groups, and no severe complications, such as venous or pulmonary thrombosis, were noted in any of the patients who received the agent. Administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
92
4
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 6 publications
6
92
4
3
Order By: Relevance
“…TEA does not influence fibrinolytic activity in vein walls [3]. Therefore, neither our study nor previous studies [5,14,15,32] observed a greater incidence of venous thrombosis in patients treated with TEA. However, the detection of DVT in our patients was based on clinical observations (thigh/calf swelling [ 3 cm and calf tenderness), followed by positive findings of antegrade venography which did not reveal the true incidence of DVT.…”
Section: Discussioncontrasting
confidence: 74%
“…TEA does not influence fibrinolytic activity in vein walls [3]. Therefore, neither our study nor previous studies [5,14,15,32] observed a greater incidence of venous thrombosis in patients treated with TEA. However, the detection of DVT in our patients was based on clinical observations (thigh/calf swelling [ 3 cm and calf tenderness), followed by positive findings of antegrade venography which did not reveal the true incidence of DVT.…”
Section: Discussioncontrasting
confidence: 74%
“…Recent evidence from the orthopaedic literature indicates a role in knee arthroplasty; [11][12][13][14][15][16][17] however, data regarding its use in hip arthroplasty are less common. [18][19][20] In our opinion, its use in orthopaedics is relatively uncommon in this country. Therefore, we performed a study to examine the results of the effects of tranexamic acid on haemoglobin falls postoperatively in patients undergoing total hip arthroplasty in our centre.…”
mentioning
confidence: 76%
“…On the contrary, Ekbäck et al described that tranexamic acid reduced perioperative and postoperative drainage bleeding [9]. Ido et al also described that postoperative blood loss in the tranexamic acid group was significantly less than in the control group in cemented THA, but they did not describe perioperative blood loss [12]. In the present study, there was no significant difference of perioperative blood loss between the two groups, but postoperative blood loss was significantly less in the tranexamic acid group than in the control group when tranexamic acid was given 5 min before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on peri-and postoperative bleeding using tranexamic acid have focused on cemented THA so far [4,9,12]. Regarding cemented THA, the femoral canal and possibly the acetabular bony beds are closed off by cement, and the pressurization of cement has a ceasing effect on blood loss from intramedullary circulation.…”
Section: Discussionmentioning
confidence: 99%